Reason and Unreason of the infanticide of Medea - Peinado Vázquez, R. Verónica (Nómadas. Critical Journal of Social and Juridical Science, 2011)
The infanticide committed by Medea in the Tragedy of Euripides is classed as a criminal act where the reasons and ruses of the protagonist play an important role. These components were traditionally studied from the signified of the name of Medea. In this essay we also studied her name but from the analysis of the signifier to look the elements (the rational and insane motivations) who drive Medea to commit the murder of her children.
Keywords: Medea; Euripides; infanticide; narcissism; madness